1996
DOI: 10.1136/hrt.75.5.455
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deaths in patients awaiting heart transplantation: impact on patient selection criteria.

Abstract: (Heart 1996;75:455-462)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As a result, an increasing number of ambulatory patients with advanced CHF are placed on transplant waiting lists. Given the limited number of donor organs, the time on the transplant waiting list has increased and is frequently more than 1 year [2]. On the other hand, Stevenson et al [3] reported that CHF patients who survive on the transplant list for more than 6 months may no longer have a prognostic advantage from cardiac transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, an increasing number of ambulatory patients with advanced CHF are placed on transplant waiting lists. Given the limited number of donor organs, the time on the transplant waiting list has increased and is frequently more than 1 year [2]. On the other hand, Stevenson et al [3] reported that CHF patients who survive on the transplant list for more than 6 months may no longer have a prognostic advantage from cardiac transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated pulmonary capillary pulmonary pressure was shown to be a poor prognosis in multivariable analyses [14]. Other important parameters directly measured with a PAC that have prognostic information are the RA pressure [15], pulmonary artery pressure [16], and resting cardiac output [17]. The elevated pulmonary artery and RA pressures represent a condition in which the right ventricle function is deteriorating due to elevated left-sided fi lling pressures.…”
Section: Clinical Usementioning
confidence: 98%
“…[5][6][7] The high values of PASP were consistent with the presence of CHF, which is associated with an increase in this parameter. [8][9][10] ASP has been shown to be a marker of mortality in CHF. 11,12 The high number of patients with EF >20% and with a DT higher than 130 msec at baseline might have contributed to the reduced morbidity rate throughout the six months of observation.…”
Section: Discussionmentioning
confidence: 99%